Episodios de reactivación del sistema de fallas del Romeral en la parte Nor-Occidental de los Andes Centrales de Colombia a través de resultados 39AR-40AR y K-AR. (2012)
Direct dating of reactivation of the San Jerónimo Fault (SJF), easternmost limit of the Romeral fault system (RFS), is presented through 39Ar-40Ar and K-Ar results in neo-formed micas and mylonitic bands of strongly hidrothermalized gabbros. Published cooling and crystallization ages from sin-tectonic magmatic rocks exposed in the western fl ank of the Central Cordillera have suggest that tectonic evolution of the paleo-fault system began since Triassic and Lower Jurassic before the installation of Central Cordillera in its present position relative to the South American margin (SOAM). The Sabaletas greenchists (Arquía complex) yields 39Ar-40Ar plateau age of 127±5 Ma and integrated ages between 102-115 Ma eventually recording the initial accommodation of the Albian-Aptian volcanosedimentary sequence of the Quebradagrande Complex to the continental margin. Direct dating of fault reactivation of SJF through 39Ar-40Ar analysis in neo-formed micas in mylonitic bands and K-Ar ages in a hidrothermalized gabbro belonging to the Quebradagrande volcanic rocks shows plateau ages ranging from 87-90 Ma in biotite and 72-81 Ma in sericite, whereas K-Ar whole rock ages in samples collected in the area of infl uence of the SJF range between 91-102 Ma. The predominance of Upper Cretaceous ages suggest that activity of the fault system rich the major and most important peak during this time spam. This age interval is most likely related to the oblique arrival and collision of the Caribbean-Colombian Oceanic Plateau (CCOP) episodically during the upper cretaceous. Final deformational episodes in the Central Cordillera and RFS are related to the collision of the Panamá-Chocó block in Early Mioceneearly Pliocene, and are recorded by 39Ar-40Ar and K-Ar ages in Mio-Pliocene intrusives along the Cauca depression.